PROFITABILITAS SEBAGAI VARIABEL INTERVENINGPADA ANALISIS LIKUIDITAS DAN UKURAN PERUSAHAAN TERHADAP KEBIJAKANÂ DIVIDEN - Kresnawati, Desi; Sartika, Farahiyah (Jurnal Manajemen, 2022)
The purpose of this research is to examine the impact of liquidity, firm size, and profitability on dividend policy, as well as the impact of profitability as an intervening variable in the relationship between liquidity, firm size, and dividend policy of manufacturing companies listed on the Indonesia Stock Exchange in the period 2018-2020. The study was done with the help of SmartPLS software and the Partial Least Square (PLS) approach. Purposive sampling was used, with as many as 65 companies participating. This study relied on secondary data. The data was gathered from a variety of sources, including the Central Statistics Agency (BPS), books, reports, journals, and other publications. The findings show that, in the period 2018-2020, liquidity and company size have no effect on dividend policy, profitability does, and profitability cannot be an intervening (bridging) factor between the effects of liquidity and firm size on dividend policy in Indonesian manufacturing companies.